PENERAPAN PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGASI (GI ) DENGAN MEDIA FOLKLORE UNTUK MENINGKATKAN SIKAP SOSIALDAN PRESTASI BELAJAR SEJARAH SISWA - Warkim, W.; Wasino, W; Suryani, Nunuk (HISTORIKA, 2016)
The purpose of this study to analyze: 1) Increased social attitudes of students with cooperative learning Group Investigation (GI) XG grade students of SMA Banyumas, 2) Improvement of learning achievement of students with a history of cooperative learning Group Investigation (GI) at XG grade high school students Banyumas country.This type of research is a classroom action research (Classroom Action Research). This research was conducted with three cycles, each cycle consisting of four phases, namely: 1) planning action, 2) the implementation of the action, 3) observation, and 4) reflection. Each cycle executed on the basis of competence. Techniques of data collection is done in three ways: 1) observation, 2) test, and 3) questionnaire.The results of the implementation of the actions done shows social attitudes questionnaire scores average initial condition 64.03%, at the end of the first cycle of 68.05%, at the end of the second cycle of 733.72%, and at the end of the third cycle of 75.03%. While the test results to learn from baseline 66.80%, at the end of the first cycle of 72.31%, 78.20% in the second cycle, and at the end of the third cycle of 82.68%, and the obtained results above the minimum value of 75. The data completeness showed an increase in the quality of learning in the classroom XG history that includes an increase in social attitudes and achievement of students learning history. Increasing students' social attitude reflected in the interaction and participation of students during the learning process, while improving student learning outcomes addressed by increasing student learning outcomes and the number of students who achieve mastery learning in each cycle, based on the results of this study concluded that the use of cooperative learning approach Investigation Group (GI) is effective for improving social attitudes and learning achievement of students in the class history XG.